2018
DOI: 10.1016/j.compfluid.2016.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Eulerian–Lagrangian simulations of dense solid-liquid suspensions settling under gravity

Abstract: We study dense solid-liquid suspensions through numerical simulations. The liquid flow is solved by the lattice-Boltzmann method on a fixed (Eulerian), cubic, uniform grid. Spherical solid particles are tracked through that grid. Our main interest is in cases where the grid spacing and the particle diameter have the same order of magnitude (Critical issues then are the mapping operations that relate properties on the grid and properties of the particles, e.g. the local solids volume fraction seen by a particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…In our previous work, it was shown that average slip velocities were virtually insensitive for the half‐width of the mapping function λ as long as λ/d1.5. The left panel of Figure confirms this for the current hindered settling simulations.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous work, it was shown that average slip velocities were virtually insensitive for the half‐width of the mapping function λ as long as λ/d1.5. The left panel of Figure confirms this for the current hindered settling simulations.…”
Section: Resultsmentioning
confidence: 99%
“…The choice of the width of the mapping function ( λ) is worthwhile investigating. Earlier research suggests a value of λ=1.5d and we will be using this as our default choice. However, we will be looking into the effects of excursions from this choice.…”
Section: Flow Systems and Simulation Methodsmentioning
confidence: 99%
See 3 more Smart Citations